Measuring The Response of Some Economic Stability Variables to Monetary Hegemony Shocks in Iraq For The Period (2004 - 2021): Mengukur Respon Beberapa Variabel Stabilitas Ekonomi Terhadap Guncangan Hegemoni Moneter di Irak Pada Periode (2004 - 2021) - Jafar, Ali Fahim (Indonesian Journal of Law and Economics Review, 2024)
This research aims to study the impact of monetary hegemony shocks on some economic growth variables To Iraq. The most important factors affecting economic growth were identified, the variables of the model are depicted; there are many independent variables while gross domestic product symbolizes the economic growth as dependent variable. The least square technique was used to estimate the parameters of the model. The unit root test and the cointegration test were used in this paper as well. Impulse response functions were computed to examine the responses of the Iraqi economy to shocks in the study period. The estimation results showed that the time series for the study adjusts after the first differences, along with evidence on the joint integration which suggested a long-run cointegrating relationship among the used variables. It was also observable that the changes in the world oil prices had economic shocks that affected the growth rate in Iraq. Highlights: Impact of monetary shocks on Iraq's economic growth. Model uses GDP as dependent variable; various independent factors analyzed. Oil price shocks influence Iraq’s growth rate. Keywords: Monetary shocks, economic growth, money supply, interest rate, exchange rate, and monetary hegemony